Analysis of Causes and Effects of Applying IAS And IFRS in Case of Mergers and Acquisitions of Banks in the Federation of Bosnia and Herzegovina - Bašić, Meliha; Jahić, Haris; Jahić, Lejla (European Journal of Sustainable Development, 2013)
One of the effect of the “stabilization and accession” process, i.e. of fulfillingrequirements for entry of the state of Bosnia and Herzegovina into the European Union,over the past few years, has been the privatization and concentration of banks’ capital,primarilythroughtheprocessoftheirmergers.1 The paper is primarily aimed at analyzing the way, causes and effects of applying IASand IFRS in mergers and acquisitions of banks in the Federation of Bosnia andHerzegovina. The presented analysis revealed the discrepancy between regulations by theBanking Agency of Federation Bosnia and Herzegovina, as the supervisory body forbanking in this part of BH and IAS and IFRS, particularly with respect to the frameworkfor financial reporting for banks, a lack of detailed disclosure prescribed by IAS andIFRS, as well as of instructions and methodology related to the processes that must beconducted. It directly resulted in unrealistic, unbjective and, naturally, insufficientlycomprehensible, and insufficiently controllable and comparable financial statements bygiven banks, before and after mergers and acquisitions. In the same time, it made it moredifficult to do business, conduct internal and external control and auditing, particularly bya regulatory body, and resulted in a series of objections by foreign controllers (IMF,IBRD). The conducted research points to problems present in practice with respect tomergers and acquisitions of banks in the Federation B-H, and provides guidelines fortheir possible solution.